Healthcare applications of pH-sensitive hydrogels based devices: a review - Hendi,A; Hassan,MU; Elsherif,M; Alqattan,B; Park,S; Yetisen,AK; Butt,H (International Journal of Nanomedicine, 2020)
pH-sensitive hydrogels have developed greatly over the past few years. This has been possible due to the synthesis of new hydrogel systems with increased sensitivity - the sensitivity of up to 10-5 pH units have already been established. Recently, pH-sensitive hydrogels have shown to be very useful for biomedical applications, such as targeted cancer treatment and treatment of skin lesions. Prolonged drug release has been made available through the use of such hydrogels. The synthesis of pH-sensitive hydrogels is also quick and cost-effective. This review presents a background on the properties of pH-sensitive hydrogels and discusses some of the hydrogels with different sensitivity ranges and their possible applications. A range of synthesis processes has also been briefly introduced along with the fabrication of different structures such as microcantilevers and contact lenses.